Footwear of Žagarė Citizens of 17th Century - Puškorius, Arūnas (Archaeologia Lituana, 2016)
There are over 7 million cultural values in Lithuanian museums. A significant part of them are archaeological findings. However, only a tiny part of them gets to the museums, i.e., usually, visually the most beautiful and representative findings. In recent years, we can see the increase in cooperation between archaeologists and restorers of archaeological findings. Therefore, the most valuable and least lasting findings come to the hands of restorers directly from the place of discovery and are immediately preserved and restored. Such are the archaeological leather footwear findings. Archaeological footwear findings are rare among the museum exhibits. Just a few Lithuanian museums exhibit archaeological footwear findings of the 14–18th centuries. Leather footwear archaeological findings are often found in only few places in Lithuania. The specific archaeological environment is the decisive factor for remaining of leather artifacts. Most of them are found in the ancient cities of Lithuania, which were major political and commercial centers in their time: Kernavė, Vilnius, Kaunas, and Klaipėda. In other cities and towns, such findings are extremely rare or not found at all. In 1990, during the archaeological research in the former Carmelite monastery territory in Kėdainiai, in Didžioji Str. No. 17, 19, 21, in the small household pit, archeologists found leather strips and footwear manufacturing spoilage from the 17th century. Supposedly, there had to be quite a large shoemaker’s holding and workshop in the surrounding area, which probably belonged to Petras Mukčius, indicated in 1686 city’s inventory. In the findings list of research report, the leather artifacts are not mentioned and their further fate is unknown. Leather footwear leftovers are also mentioned among the findings of 2008 archaeological excavations in Ukmergė, in Utenos Str. Ten leather findings were inventoried in archaeological excavations report from the first half of the 18th century: footwear details, leather strips, straps fragments. Quite exceptional exhibits are the restored archaeological findings from Kurtuvėnai (Šiauliai district) St. Apostle Jacob’s Church, which are stored in Šiauliai “Aušra” museum and were restored in Pranas Gudynas Restoration Centre of Lithuanian Art Museum. In the basement of this church, in disintegrated crypt, the remains of two men from the 18th century were discovered. The surviving footwear was restored – it is a pair of boots of very complex construction, which were thoroughly made from bovine leather of vegetable tanning. As we can see, the footwear findings are rarely found during periphery archaeological excavations. Therefore, the footwear findings of Žagarė found during archaeological researches gained special attention from researchers. According to Algimantas Miškinis, the renaissance rectangular market square of New Žagarė was probably formed in the second half of the 16th century. It is certain, that even in the first half of the 19th century, there stood wooden trading stalls, which were destroyed by a fire that devastated the town in 1881. After the Second World War, in 1947, market places were demolished and trees were planted in the square. Since 1997, archaeological excavations of various scope were carried out in the territory of the square and its surroundings. Archaeological footwear findings were detected only during the last archaeological excavations in the market square, in 2012. The findings came directly from archaeological sites to Pranas Gudynas Restoration Center of Lithuanian Art Museum. Two different preservation methods are applied to leather findings: 1. dressing, 2. the treatment with solutions of low molecular weight hydrophilic compounds (PEG-400, 600 or glycerol). These methods help to maintain leather softness and consolidate and protect it from atmospheric moisture fluctuations. Leather Dressing is characterized by the fact that it limits or cancels the possibility of re-preservation of findings. Therefore, the preservation with PEG solution in water was chosen. In addition, the findings were wet and sufficiently soft. To preserve the leather findings we used the 10% PEG-400 solution in water-alcohol mixture (1:1) with 3% antiseptic Boramon C30 additive. After the preservation of leather and disbandment of details, cracks and laminated leather layers were glued together with acrylic copolymer A-45K acetone solution. Three different molecular weight polyethylene glycol solutions, PEG-400, 1500 and 5000 were used to preserve wood. The wood surface was covered with a protective coating of wax balsam Pronto. Most of the information about the footwear of the late historic times, which interests the researchers, is best accumulated by conserving findings before their restoration, i.e., by connecting the details and thus restoring the image close to its authentic state. When producing leather articles of complex design, the craftsmen used not only skin, but also other kinds of materials – wood, threads, textile or metal. The author of this publication drew all footwear details, determined the connection seams of the details, indicated the animal’s skin type, measured the leather thickness, ascertained footwear design, identified patterns and determined the footwear sizes according to the standard used in Lithuania. Also, the research set out to determine the timber type of certain footwear parts. In total, 2 low-cut shoes (r. s. No. 116, 178) and 3 mules (r. s. No. 118, 177 and 179) were restored. Horse skin was used for the treadsole of the low-cut shoe (r. s. No. 116), size 25 (baby footwear), while cattle skin was used for the upper part. The inlay, which was made from the part of another insole, improved shoe wearing and probably solved the problem of too large footwear. Low-cut shoe (r. s. No. 178) (Fig. 2) – the only decorated footwear finding, size 33, with low heel. All details are made from bovine skin of various thickness. Low-cut shoe is attached to the leg by front lacing. Mule (r. s. No. 118), size 33, with medium height middle heel. All leather parts are made from bovine skin but of a different thickness. Birch wood was used as filler. The unusual way of insole stitching suggests that the artist saved both materials and time. Mule (r. s. No. 177), size 39, has a pointed toe part and low heel. This footwear finding has the most intricate construction of this complex. Animal skin of different age was used to make this footwear. Based on the design and quality of materials used, it can be said that according to the price it had to be the most expensive footwear. Mule (r. s. No. 179) remained incomplete, a part of heel had been torn apart and some details are missing, it could have been size 38–39. All details were made from bovine skin of various thicknesses. The historic examples of the 17th century footwear are exhibited in major museums around the world, also the museums specialising only in the history of the development of footwear have accumulated historical footwear of this period. However, the vast majority of the exhibits are luxurious footwear of the rich. We see quite a different picture concerning footwear of ordinary people – peasants and townspeople. This footwear was often worn out and thrown away, therefore there are no historical findings. The largest amount of information about these findings is provided precisely by archaeological material and iconography. Comparing the Žagarė urban archaeological findings with the iconography data of Western Europe, it can be said that three mules that were found during the research can confirm the fact that this type of footwear at that time was very popular and well-liked among both rich and ordinary citizens. Footwear – (except for mule r. s. No. 177, which has a distinct design and sewing technique) low-cut shoes and mules, which were discovered, have a similar design, and a very similar sewing style. It can be assumed that the latter footwear could be made by the same craftsman.